Domestic climate policies and the WTO - Zhang, Zhong Xiang (2004)
Discusses carbon/energy taxes, subsidies, energy efficiency standards, eco-labels, government procurement policies, and explores the potential interaction between these domestic climate policies and WTO rules. Highlights their potential conflicts, and argues that such conflicts can be avoided or at least minimised if WTO rules are carefully scrutinised, and efforts are made early on to ensure that the proposed climate policies comply with them. Suggests an early process of pursuing consultations between WTO members and the Parties to the Climate Change Convention and points to the need of further exploring ways to enhance synergies between the trade and climate regimes.